2018
DOI: 10.1016/j.hoc.2017.11.002
|View full text |Cite|
|
Sign up to set email alerts
|

Emerging Therapies

Abstract: At present, the only definitive cure for β-thalassemia is a bone marrow transplant (BMT); however, HLA-blood-matched donors are scarcely available. Current therapies undergoing clinical investigation with most potential for therapeutic benefit are the β-globin gene transfer of patient-specific hematopoietic stem cells followed by autologous BMT. Other emerging therapies deliver exogenous regulators of several key modulators of erythropoiesis or iron homeostasis. This review focuses on current approaches for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…118 The ligand traps sotatercept and luspatercept have shown promising results in phase 2 studies with significant reduction in transfusion requirement for TDT patients and increase in hemoglobin level in NTDT patients; data from randomized clinical trials are awaited. 119,120 Hepcidin agonists are also being evaluated for their ability to prevent iron overload and improve anemia in b-thalassemia patients. 121 Reductions in transfusion requirement and subsequent prevention of iron overload in TDT and improvement in anemia with prevention of iron overload in NTDT will surely translate to reduced morbidity risk.…”
Section: Future Prospectsmentioning
confidence: 99%
“…118 The ligand traps sotatercept and luspatercept have shown promising results in phase 2 studies with significant reduction in transfusion requirement for TDT patients and increase in hemoglobin level in NTDT patients; data from randomized clinical trials are awaited. 119,120 Hepcidin agonists are also being evaluated for their ability to prevent iron overload and improve anemia in b-thalassemia patients. 121 Reductions in transfusion requirement and subsequent prevention of iron overload in TDT and improvement in anemia with prevention of iron overload in NTDT will surely translate to reduced morbidity risk.…”
Section: Future Prospectsmentioning
confidence: 99%
“…Drugs that limit iron absorption and improve anemia are showing very promising results in preclinical studies. 12 Additional drugs that target oxidative stress (like peroxiredoxin-2 agonists) and erythroid cell metabolism (like Glycine Transporter Type I Inhibitor or Pyruvate kinase agonists) are being investigated. Preclinical studies indicate that combinatorial therapies could further improve anemia.…”
Section: New Technologies For Anemia and Related Disordersmentioning
confidence: 99%
“…14 The elucidation of these pathways and their association with disease led to the development of pharmacological compounds that increase hepcidin expression, mimic its activity, or decrease ferroportin activity, which can decrease iron absorption and improve iron overload in primary and secondary forms of hemochromatosis (Figure 1A). 15,16 Intriguingly, the same drugs also showed beneficial effects on anemia in animal models of nontransfusion-dependent thalassemia (Figure 1A). 13,17,18 In this case, it was observed that these drugs not only decreased iron absorption, but also erythroid iron intake.…”
mentioning
confidence: 87%